ERPS TO SUBCLASSES OF NOUNS AND VERBS - Petrek, Josef (Biomedical papers, 2004)
The present findings show the existence of significant differences in latency and amplitude of some waves of ERPs to three subclasses of nouns or verbs. Latency LP3 of ERPs to action verbs was shorter than latency of the same wave to abstract verbs. In nouns the relation was a similar (manipulable objects versus abstract ones). The amplitude of early positive components (P1, P2) and BN3 wave also depended on semantic attributes of nouns and verbs. Some waves of ERPs to motion verbs in our experiment had significantly higher amplitude than the same waves of ERPs to nonmanipulable objects. Also revealed was interaction between some ERP features and the subject's gender. It was primarily the amplitude of BP2, the size of which depended on gender in all cases - BP2 amplitude was significantly higher in females then in males. In the other components (BP1, BP4, BN2 and BN4) there were fewer significant differences and if they do occurred, then their amplitude was higher in males than in females. In some cases, gender also affected latency of waves LP2, LN1 and LN4 of ERPs to the same noun or verb subclass - latencies of these waves were shorter in females.
Keywords: ERPs/Word subclasses/Gender/Site of recording electrode